Practical energy efficiency techniques to the industry - M. M. Ahmed, Musse Mohamud Ahmed; Sheroz Khan, Sheroz Khan (2010)
This paper presents practical research work that has been done on energy efficiency for assessing and carrying out energy efficiency exercises for electric motors (induction & synchronous electrical motors), lights, fans-blowers and other appliances used by the current industry. The main purpose works is to save energy and save energy costs. Practical energy consumption assessment has been developed to come up with proper energy efficiency techniques for the energy consumed facilities in order to reduce energy consumption bills, improve energy efficiency and enhance lifespan of the equipment. Some results based on energy efficiency will be shown in this paper.